Combination of cisplatin, Hedyotis corymbosa L. and Tinospora crispa extracts as a new therapy for breast cancer cells 4T1 through in vitro induction and cell cycle modulation - Rollando Rollando; Muhammad Hilmi Afthoni (Pharmaciana, 2020)
Cisplatin is a chemotherapeutic agent with varying side effects. Berberine compounds in Tinospora crispa and ursolic acids in Hedyotis corymbosa L are known to have high cytotoxic activities. This study was aimed to examine the effects of the combination of cisplatin, the ethanolic extract of Hedyotis corymbosa L.(EEHC), and the ethanolic extract of Tinospora crispa roots (EETC) on enhanced breast cancer cell sensitivity by apoptotic induction and cell cycle modulation. Cytotoxic effects were tested using the MTT assay in breast cancer cells, 4T1. The combination test of cisplatin and the extracts yielded combination index (CI) and cell viability, and its effects on the induction of apoptosis and cell cycle modulation were observed by the flow cytometry method. The results of the cytotoxic test showed CI of less than one for 1 mg/mL EEHC, 6 mg/mL EETC, and 1.68 mg/mL cisplatin. The EEHC-EETC-cisplatin combination accumulated cells in the S phase (29.98%) and induced apoptosis in 4T1 cells. It proves that EEHC and EETC can be developed as co-agents with cisplatin to improve the effectiveness of breast cancer chemotherapeutic treatment.